PENGABDIAN KKN-MANDIRI TEMATIK KELURAHAN ONEKORE KABUPATEN ENDE - Yulita Londa; Yulita Tanda; Yohanes F Senda; Yanuaris B Gabe; Sirilus Sandy Banda; Kristian E Turu More; Hedwig Hendra Tegu Rani (LPPM Universitas Flores, 2021)
The general theme of the 2020 Community Service Program is “Community Empowerment”. Meanwhile, the special theme is